2017
DOI: 10.1158/1078-0432.ccr-16-0725
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Benefit of Hypoxia-Activated Intra-arterial Therapy with Evofosfamide in Liver Cancer

Abstract: Purpose To evaluate safety and characterize anticancer efficacy of hepatic hypoxia-activated intraarterial therapy (HAIAT) with evofosfamide in a rabbit model. Experimental Design VX2-tumor-bearing rabbits were assigned to 4 intraarterial therapy (IAT) groups (n=7/group): 1) saline (control); 2) evofosfamide (Evo); 3) doxorubicin-Lipiodol emulsion followed by embolization with 100-300μm beads (conventional, cTACE); or 4) cTACE and evofosfamide (cTACE+Evo). Blood samples were collected pre-IAT and 1/2/7/14 da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…In this study, we observed an increase in hypoxia upon evofosfamide treatment in both CT-1 and CT-2 experiments. Though this finding is in agreement with a previous finding where evofosfamide enhanced hypoxia in liver cancer xenografts after 14 days of treatment, other studies have reported reduction in tumor hypoxia in renal cell carcinoma and leukemia in response to evofosfamide treatment [33] , [34] , [35] . These contradictory findings indicate the possibility that the effect of evofosfamide on the extent of tumor hypoxia may depend upon factors such as tumor type and dose and duration of the therapy.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we observed an increase in hypoxia upon evofosfamide treatment in both CT-1 and CT-2 experiments. Though this finding is in agreement with a previous finding where evofosfamide enhanced hypoxia in liver cancer xenografts after 14 days of treatment, other studies have reported reduction in tumor hypoxia in renal cell carcinoma and leukemia in response to evofosfamide treatment [33] , [34] , [35] . These contradictory findings indicate the possibility that the effect of evofosfamide on the extent of tumor hypoxia may depend upon factors such as tumor type and dose and duration of the therapy.…”
Section: Discussionsupporting
confidence: 93%
“…of three independent experiments. activity (Sun et al, 2012) and augments the efficacy of approved therapies, including radiation (Peeters et al, 2015;Lohse et al, 2016;Jamieson et al, 2018;Takakusagi et al, 2018), immune checkpoint blockade (Jamieson et al, 2018;Jayaprakash et al, 2018), bortezomib (Hu et al, 2013), mTOR (mammalian target of rapamycin) inhibitors (Sun et al, 2015), transarterial chemoembolisation (Duran et al, 2017), and various cytotoxic agents (Liu et al, 2012;Zhang et al, 2016;Haynes et al, 2018). Clinically, evofosfamide is well tolerated (Weiss et al, 2011) and was active in combination with gemcitabine for advanced pancreatic cancer (Borad et al, 2015) and doxorubicin for soft-tissue sarcoma (Chawla et al, 2014) in phase 2 randomized and single-arm studies, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Evofosfamide is a clinical-stage hypoxia-activated prodrug designed to target the DNA-crosslinking nitrogen mustard bromo-iso-phosphoramide (Br-IPM) to regions of hypoxia (37), leading to DNA damage, γH2AX phosphorylation, cell cycle arrest, and cleavage of caspase-3 and -6 (38)(39)(40). Despite narrowly missing its primary phase 3 overall survival (OS) endpoint with gemcitabine for advanced pancreatic adenocarcinoma (41), evofosfamide shows abundant evidence of preclinical (40,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) and clinical activity (52,53). However, evofosfamide has not been comprehensively investigated for HNSCC.…”
Section: Introductionmentioning
confidence: 99%